Dynamic effects induced by the impact of debris flows on protection barriers. Issue 1 (March 2019) - Marchelli, Maddalena; De Biagi, Valerio
Debris flow is a transient phenomenon that causes large disasters. Retaining systems, whose design is still nowadays a crucial issue, can mitigate this risk. Multiple surges can arise during this phenomenon; thus, an accurate analysis might consider the impact force time histories rather than only its maxima. The aim of this work is to analyze the effects of the interaction between the debris and the barrier during one surging phenomenon. A discrete element model models the granular motion and the interaction between the debris and a rigid open barrier set at the end of the channel. The estimated interaction force time history is then used as input impact force for the dynamic structural analyses of the piles. A total of 12 different structural sections are adopted and the internal forces at the base are critically compared. It results that the first mode vibration period is the parameter that largely affects the behavior of the piles.